Ofloxacin induced hallucinations in a 6 years old child: A case report - Prashant Chaudhari; Sagar Karia; Nilesh Shah; Avinash De Sousa (Telangana Journal of Psychiatry, 2019)
Ofloxacin is a commonly used fluoroquinolone antibiotic in adults as well as children. It is generally safe and well tolerated though rare neurological and psychiatric adverse reactions have been reported with Ofloxacin. We report a case of a 6 years old child who developed hallucinations after being started on Ofloxacin and which resolved on discontinuation of the drug.